Warm temperatures increase population growth of a nonnative defoliator and inhibit demographic responses by parasitoids. Issue 11 (2nd September 2020) - Ward, Samuel F.; Aukema, Brian H.; Fei, Songlin; Liebhold, Andrew M.
Abstract: Changes in thermal regimes that disparately affect hosts and parasitoids could release hosts from biological control. When multiple natural enemy species share a host, shifts in host–parasitoid dynamics could depend on whether natural enemies interact antagonistically vs. synergistically. We investigated how biotic and abiotic factors influence the population ecology of larch casebearer ( Coleophora laricella ), a nonnative pest, and two imported parasitoids, Agathis pumila and Chrysocharis laricinellae, by analyzing (1) temporal dynamics in defoliation from 1962 to 2018, and (2) historical, branch‐level data on densities of larch casebearer and parasitism rates by the two imported natural enemies from 1972 to 1995. Analyses of defoliation indicated that, prior to the widespread establishment of parasitoids (1962 to ~1980), larch casebearer outbreaks occurred in 2–6 yr cycles. This pattern was followed by a >15‐yr period during which populations were at low, apparently stable densities undetectable via aerial surveys, presumably under control from parasitoids. However, since the late 1990s and despite the persistence of both parasitoids, outbreaks exhibiting unstable dynamics have occurred. Analyses of branch‐level data indicated that growth of casebearer populations, A. pumila populations, and within‐casebearer densities of C. laricinellae —a generalist whose population dynamics are likely also influenced by use of alternative hosts—were inhibited by density dependence, with high intraspecific densities in one year slowing growth into the next. Casebearer population growth was also inhibited by parasitism from A. pumila, but not C. laricinellae, and increased with warmer autumnal temperatures. Growth of A. pumila populations and within‐casebearer densities of C. laricinellae increased with casebearer densities but decreased with warmer annual maximum temperatures. Moreover, parasitism by A. pumila was associated with increased growth of within‐casebearer densities of C. laricinellae without adverse effects on its own demographics, indicating a synergistic interaction between these parasitoids. Our results indicate that warming can be associated with opposing effects between trophic levels, with deleterious effects of warming on one natural enemy species potentially being exacerbated by similar impacts on another. Coupling of such parasitoid responses with positive responses of hosts to warming might have contributed to the return of casebearer outbreaks to North America.